2007
DOI: 10.1521/suli.2007.37.5.593
|View full text |Cite
|
Sign up to set email alerts
|

A Decrease in Suicide Rates in Japanese Rural Towns after Community‐Based Intervention by the Health Promotion Approach

Abstract: A community-based intervention study for suicide prevention was conducted in six towns (total population 43,964) in Akita Prefecture of Japan according to a quasi-experimental design to reduce suicide rates in rural towns. Public awareness raising activities using a health promotion approach emphasizing the empowerment of residents and civic participation were conducted. The welfare measures of promoting a sense of purpose among senior citizens and creating a community network were also taken. As a result, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 9 publications
0
38
0
3
Order By: Relevance
“…Suicide was reduced for females (by 76%), but not for males, and there was no change at all in the control area. Motohashi, Kaneko, Sasaki, and Yamaji (2007) reported on a programme in six towns in Akita Prefecture, where the suicide rate in the intervention towns decreased from 71/100,000 before (1999) to 34 after (2004) intervention. The corresponding rates in the control towns were 48 and 49.…”
Section: The Third Step Towards a Global Movementinternational Dissemmentioning
confidence: 99%
“…Suicide was reduced for females (by 76%), but not for males, and there was no change at all in the control area. Motohashi, Kaneko, Sasaki, and Yamaji (2007) reported on a programme in six towns in Akita Prefecture, where the suicide rate in the intervention towns decreased from 71/100,000 before (1999) to 34 after (2004) intervention. The corresponding rates in the control towns were 48 and 49.…”
Section: The Third Step Towards a Global Movementinternational Dissemmentioning
confidence: 99%
“…Several studies [24,25] indicated that socioeconomic factors affect the suicide mortality rate in Japan; low income and conditions created by economic depression emerged as major factors. Recent studies have shown that a suicide prevention campaign has been effective in reducing the number of suicides in various areas in Japan, including Akita Prefecture in the Tohoku region [26,27].…”
Section: Current Status Of the Literaturementioning
confidence: 99%
“…To tackle this problem, systematic intervention for suicide prevention has been conducted with a clear focus on community-based health promotion in this and other prefectures in the Tohoku region. For example, a community-based intervention was conducted in Akita Prefecture between 2001 and 2004 [27]. This was a nonrandomized control trial based on a quasiexperimental design, consisting of 43,963 residents in six towns as the intervention group and 297,071 residents in the other towns located in Akita Prefecture as the control group [27].…”
Section: Community-based Intervention For Suicide Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effect of late-life mental illness on physical health, social support systems, and overall functioning is a major burden in elderly people (WHO, 2012). Additionally, mental illnesses are preventable risk factors for mortality, particularly suicides linked to mental illness (Motohashi, Kaneko, Sasaki, & Yamaji, 2007). The prevalence of comorbid physical and mental illness increases with age, and the incidence of mental illness increases when physical illness becomes more pronounced (Barnett et al, 2012).…”
Section: Introductionmentioning
confidence: 99%